2009
DOI: 10.1186/1749-8546-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fructus Piperis Longi extract on fibrotic liver of gamma-irradiated rats

Abstract: Background: A major biomarker for liver fibrosis is transglutaminase which catalyzes cross-linking of epsilon-amines and alpha-glutamyl residues among amino acids leading to fibrosis. Fructus Piperis Longi is a common herb used in Chinese medicine. The present study evaluates the role of the ethanol extract of Fructus Piperis Longi in the modulation of liver function in liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…These findings are consistent with previous investigations which indicated that TAA caused a significant decrease in the levels of liver SOD and GSH [12, 55, 56]. TAA is a well-known liver hepatotoxicant, the hepatotoxicity results from its metabolic conversion to free radical products: thioacetamide sulfoxide and thioacetamide-S, S-dioxide which attacks microsomal lipids leading to their peroxidation and production of reactive oxygen species (ROS), such as the  H 2 O 2 , super oxide anion O 2 − , and the hydroxyl radical.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are consistent with previous investigations which indicated that TAA caused a significant decrease in the levels of liver SOD and GSH [12, 55, 56]. TAA is a well-known liver hepatotoxicant, the hepatotoxicity results from its metabolic conversion to free radical products: thioacetamide sulfoxide and thioacetamide-S, S-dioxide which attacks microsomal lipids leading to their peroxidation and production of reactive oxygen species (ROS), such as the  H 2 O 2 , super oxide anion O 2 − , and the hydroxyl radical.…”
Section: Discussionsupporting
confidence: 94%
“…The obtained data revealed significant increase in AST, ALT and GGT activities in irradiated rats throughout the experimental period. The observed increase in the hepatotoxicity biomarkers agree with the previous studies (Ashry and Hussein, 2007;Mansour and El-Kabany, 2009). The increase in the level of liver enzymes might be a result of the damage in hepatic cellular membranes (Gaur and Bhatia, 2009), impair of intrahepatic and extrahepatic bile flow, injury of hepatobiliary, or destruction of erythrocyte induced by irradiation (Singh et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, antioxidative activity of the KSOP1009 could be responsible for its neuroprotective effects against cytotoxicity of A␤42. Several studies have reported the antioxidant effects of the herbs that comprise KSOP1009 (Yokozawa et al, 1995;Park et al, 2006;Chaieb et al, 2007;Jeong et al, 2009;Mansour and El-Kabany, 2009). Given that oxidative stress has been implicated in AD (Emerit et al, 2004) and induced cell death via JNK activation (Shen and Liu, 2006), the antioxidative activity of the KSOP1009 may inhibit hyperactivation of JNK, thereby protecting cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%